ACCELERATING PREFABRICATED CONCEPT IN RESIDENTIAL PROJECTS; HURDLES AND DRIVERS - Ahmad, Abd Jalil; Shazwan, Mohamed Shaari; Areefah Batrisyia, Norhisham (2021)
Providing adequate proper housing is one of Malaysian government agenda towards becoming a develop nation in Wawasan Kemakmuran Bersama 2030. Under previous Construction Industry Transformation Plan (CITP) 2015, the government aims to provide enough and comfortable residential to all citizen, and achieve a better standard of construction where prefabrication concept in housing replaces the conventional concept. The advantages of prefabrication concept are numerous including reducing the dependency on foreign labours, better quality, cost saving and speed. So long our local residentials have already familiar with conventional method, thus shifting into prefabricated concept is no easy task. Numerous efforts have been taken by Construction Industry Development Board of Malaysia (CIDB) and the government to ensure the prefabricated residential will become the preferred choice by developers. However, the uptake has been very slow and the target seem likely unachievable due to many reasons. Therefore, there is an urgency to know what are the difficulties that the industry facing in adopting prefabricated housing and what steps can be taken to overcome those problems. This paper discusses the barriers in implementing prefabricated concept in residential and the drivers that can speed up the application. The discussion based on published journals and articles that prioritize the views from all major players in prefabricated residential projects including contractors, developers, clients, consultants and prefabrication manufacturers and installers. This research contributes to the body of knowledge by revealing the true reason of why prefabricated housing is hard to be implemented, where the arguments combine the views from all major players. This study also provides steps to solve the problems taken from experience from other successful countries.